2010
DOI: 10.1542/peds.2009-0271
|View full text |Cite
|
Sign up to set email alerts
|

Current Pediatrician Practices in Identifying High-risk Behaviors of Adolescents

Abstract: Pediatricians believed it is important to deliver reproductive health services, and most addressed adolescent sexual activity at preventive care visits but did not routinely address homosexuality/sexual identity. Counseling and testing practices varied by physician characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
77
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 14 publications
5
77
1
Order By: Relevance
“…In a national survey of the pediatric ED providers, <25% of pediatric ED physicians and staff reported that they had rapid HIV testing available in the ED, and 82.5% reported that they did not believe or were unsure whether their institution had a policy or guideline about rapid HIV testing [39]. It is necessary to increase the level of comfort for pediatric providers in addressing HIV screening in pediatric EDs to efficiently confront the HIV epidemic among American youth [3,40]. …”
Section: Discussionmentioning
confidence: 99%
“…In a national survey of the pediatric ED providers, <25% of pediatric ED physicians and staff reported that they had rapid HIV testing available in the ED, and 82.5% reported that they did not believe or were unsure whether their institution had a policy or guideline about rapid HIV testing [39]. It is necessary to increase the level of comfort for pediatric providers in addressing HIV screening in pediatric EDs to efficiently confront the HIV epidemic among American youth [3,40]. …”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is a developmental stage associated with increased risk-taking behaviors that contribute to negative sexual health outcomes. 1,2 The 2011 Youth Risk Behavior Survey documented the prevalence of sexual risk behaviors among US high school students. This survey showed that 47% of students in grades 9 to 12 have ever had sexual intercourse and 40% of currently sexually active high school students did not use a condom at their last sexual intercourse, 3 indicating that many adolescents are at risk for pregnancy and sexually transmitted infections (STIs), including HIV.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, data from a 2005 survey suggest that few of the academy's members routinely discuss sexual orientation with patients during preventive care visits. 12 Furthermore, it is unclear what questions care providers should ask to identify at-risk sexual minority girls. The American Academy of Pediatrics and others have suggested possible patient interview questions that address sexual identity, sexual attraction, romantic behavior, or sexual behavior.…”
mentioning
confidence: 99%